2011
DOI: 10.1007/s12031-011-9637-9
|View full text |Cite
|
Sign up to set email alerts
|

Making Connections: Pathology and Genetics Link Amyotrophic Lateral Sclerosis with Frontotemporal Lobe Dementia

Abstract: Over the last couple of decades, there has been a growing body of clinical, genetic, and histopathological evidence that similar pathological processes underlie amyotrophic lateral sclerosis (ALS) and some types of frontotemporal lobe dementia (FTD). Even though there is great diversity in the genetic causes of these disorders, there is a high degree of overlap in their histopathology. Genes linked to rare cases of familial ALS and/or FTD, like FUS, TARDBP, OPTN, and UBQLN2 may converge onto a unifying pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 101 publications
(152 reference statements)
0
52
0
6
Order By: Relevance
“…We note that the motor neuron phenotype and pathology are not recapitulated in these mice. However, this does not appear to be unusual, because mutations in several genes, including C9ORF72, VCP, FUS, TDP43, or UBQLN2 can cause either ALS or FTD, or both, in human patients (16). It is also worth noting that mouse motor neurons may be more resistant to the same pathogenic assaults affecting human motor neurons.…”
Section: Discussionmentioning
confidence: 93%
“…We note that the motor neuron phenotype and pathology are not recapitulated in these mice. However, this does not appear to be unusual, because mutations in several genes, including C9ORF72, VCP, FUS, TDP43, or UBQLN2 can cause either ALS or FTD, or both, in human patients (16). It is also worth noting that mouse motor neurons may be more resistant to the same pathogenic assaults affecting human motor neurons.…”
Section: Discussionmentioning
confidence: 93%
“…5 In spite of the phenotypic heterogeneity found in ALS, ALS/ FTLD and PDB and related disorders such as IBMPFD and POAG, the discovery of mutations in overlapping candidate genes, such as VCP, UBQLN2, CHMP2B and OPTN, points to a common pathogenic mechanism affecting the formation and clearance of misfolded proteins. 2 We previously reported that the genotypes of protein disulphide isomerase (P4HB), a redox enzyme that reduces formation of aberrant disulphide bonds, were associated with survival time of FALS, 28 supporting the hypothesis that factors interfering with proteostasis may modify disease progression and can be considered as therapeutic targets for ALS. The investigation of p62/SQSTM1 mutations in multiple cohorts provides further support for their contribution to a significant predisposition to disease in ALS.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, mutations in several components of protein homeostasis, such as UBQLN2, charged multivesicular body protein 2B (CHMP2B), OPTN and valosin containing protein (VCP), are also present in less prevalent forms of ALS and ALS/FTD. 2 Interestingly, mutations in OPTN and VCP are also seen in other allelic forms characterised by TDP-43-positive polyubiquitinated inclusions, primary open angle glaucoma (POAG), and inclusion body myopathy with Paget's disease of bone and frontotemporal dementia (IBMPFD), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Bu iki hastalık grubunda VBM ile serebellumda spesifik patternlerde subrejyonel atrofi tespit edilmiştir 33 . ALS ve FTD ayrımında MRI ve MRS teknikleri kullanılabilmekle birlikte kombine hastalıkta (ALS ve FTRD) kullanıldıklarında bu iki hastalığın tek bir patolojik sürece ait farklı özellikler gösterdikleri saptanmıştır 1,25,34 .…”
Section: Görüntülemeunclassified
“…Bu inflamasyonu azaltmak, büyüme faktörlerini artırmak ile mümkün olabilir 25 . Parkinson ve Alzheimer hastalığında olduğu gibi ALS'de de non-nöronal hücrelerin nöronal hücre kaybına katkıda bulunduğu düşünülmektedir 9,20 .…”
Section: Güncel Tedavi Yaklaşımlarıunclassified